Pengaruh Perputaran Modal Kerja, Struktur Modal Dan Likuiditas Terhadap Profitabilitas Perusahaan Industri & Chemical di Bursa Efek Indonesia - Tania Iskandar; Emrinaldi Nur Dp; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to obtain empirical evidence about the effect of working capital turnover, capital structure and liquidity to profitability of industry & chemical company listed in Indonesia Stock Exchange.The population of this study was the entire industry & chemical companylisted in Indonesia Stock Exchange. While the sample consists of industrial & chemical companies listed in Indonesia Stock Exchange in 2008 to 2010. Sampling method used in this study is purposive sampling method, where the sample is selected using specific criteria, in accordance with these criteria, the sample was 45 companies. Analysis of data using multiple linear regression model.The results of this study is Working Capital Turnover has no effect onprofitability (Return On Asset). Company's ability to meet obligations over the medium and long term (Debt to Equity Ratio) has a negative and significant impact on profitability (ROA). Liquidity (Current Ratio) has a positive but not significant effect on profitability (ROA).Keywords: Working Capital Turnover, Debt to Equity Ratio, Current Ratio, Return on Assets